Pembelajaran Bentuk Geometri Anak Usia 5–6 Tahun melalui Media Realita di RA Al Falah Banyuwangi - Ninik Finalita Ficia; Sigit Purnama; Sibawaihi Sibawaihi (Lembaga Yasin AlSys, 2026)
The low level of young children’s understanding of geometric shapes, which are generally still taught abstractly through two-dimensional images, highlights the need for more concrete and meaningful instructional approaches. This study aimed to describe the process and outcomes of learning geometric shapes through the use of real-object instructional media (media realita) for children aged 5–6 years at RA Al Falah Banyuwangi. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation over four weeks across eight learning sessions. The findings showed that the use of real-object media enhanced children’s enthusiasm, active participation, and understanding of the concepts of circles, triangles, and squares. Children were better able to identify shapes through tangible objects that could be touched and directly manipulated, making the learning process more meaningful by engaging sensorimotor experiences. This study contributes to strengthening concrete experience-based learning in early childhood education, particularly in developing foundational geometric concepts.